2016
DOI: 10.1038/srep34614
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nuclear localisation signal of O-GlcNAc transferase and its nuclear import regulation

Abstract: Nucleocytoplasmic O-GlcNAc transferase (OGT) attaches a single GlcNAc to hydroxyl groups of serine and threonine residues. Although the cellular localisation of OGT is important to regulate a variety of cellular processes, the molecular mechanisms regulating the nuclear localisation of OGT is unclear. Here, we characterised three amino acids (DFP; residues 451–453) as the nuclear localisation signal of OGT and demonstrated that this motif mediated the nuclear import of non-diffusible β-galactosidase. OGT bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 49 publications
3
44
0
Order By: Relevance
“…OGT has three isoforms that differ in the number of tetratricopeptide repeats (TPRs) they harbor at their N terminus, a well-described protein-protein interaction-mediating domain [49]. mOGT has an Nterminal mitochondrial localization sequence, whereas ncOGT contains a nuclear localization sequence between its TPRs and the catalytic domain located at the C terminus [51,52]. The OGT isoforms localize to different compartments of the cell.…”
Section: Regulation Of O-glcnacylationmentioning
confidence: 99%
See 3 more Smart Citations
“…OGT has three isoforms that differ in the number of tetratricopeptide repeats (TPRs) they harbor at their N terminus, a well-described protein-protein interaction-mediating domain [49]. mOGT has an Nterminal mitochondrial localization sequence, whereas ncOGT contains a nuclear localization sequence between its TPRs and the catalytic domain located at the C terminus [51,52]. The OGT isoforms localize to different compartments of the cell.…”
Section: Regulation Of O-glcnacylationmentioning
confidence: 99%
“…Regulation may in part, therefore, be governed by (the number of) these TPR repeats. Deletion of this sequence prevents transport of ncOGT into the nucleus, resulting in an increase of cytosolic O-GlcNAcylation [51]. Short OGT (sOGT) and nucleocytoplasmic OGT (ncOGT) are found in the nucleus and cytoplasm, whereas mitochondrial OGT (mOGT) is found exclusively in mitochondria [50].…”
Section: Regulation Of O-glcnacylationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first study demonstrated that Ser20 phosphorylation by checkpoint kinase 1 (Chk1) is essential for localization of OGT to midbodies during cytokinesis in HeLa cells , and the second study determined that phosphorylation by calcium/calmodulin‐dependent kinase (CaMK) II altered the pattern of O‐GlcNAcylation in hepatocytes . Three recent studies have identified several sites of O‐GlcNAcylation on OGT isoform 4 , two sites at the N terminus (Ser03, Ser04) of OGT (Isoform 1 and 3) , and one site at Ser389 on OGT (Isoform 1) . The latter site has been implicated in promoting nuclear import of OGT in HeLa cells.…”
Section: : Purification and Cloning Of The O‐glcnac Transferasementioning
confidence: 99%